Universal and Idioethnic Characteristics of Proverbs and Sayings with Zoonyms in the English and Kazakh Languages - Mazhitayeva, S.M.; Omasheva, Z.; Tazhikeyeva, A.; Kadyrov, Z.; Talaspayeva, Z.; Otynshina, S. (Canadian Center of Science and Education, 2015)
The article is devoted to the universal and idioethnic characteristics of proverbs and sayings with zoonyms in the English and Kazakh languages. Applying comparative, statistical and component methods in the analysis of lexical structure of more than 2 thousand proverbs and sayings, the authors identified universal and idioethnic characteristics inherent in each of the ethnic groups, correlation of the images of zoonyms in proverbs and sayings of the English and Kazakh languages.
Keywords: ethnolinguistics; zoonym; image; proverbs and sayings with zoonyms in the English and Kazakh languages